Pemanfaatan Media Visualisasi dalam Pengenalan Ekosistem Pesisir Bagi Siswa SMP Negeri 1 Teupah Selatan - Najmi, Nurul; Lisdayanti, Eka; Rahmawati; Rahma, Endah Anisa (Universitas Serang Raya, 2025)
Knowledge about coastal and marine ecosystems is very important to be introduced to coastal communities, including students. Basic education about coastal and marine ecosystems is carried out for students to help increase understanding and environmental awareness from an early age. The service was carried out on the coast of the Simeuleu Islands, precisely SMP Negeri 1 Teupah Selatan, Simeulue Islands Regency. The implementation of this service involved a team of teachers, directors, and assistants who ensured the activities went well. In addition, 52 students participated, divided into 22 boys and 30 girls. The service method of introducing coastal and marine ecosystems at the junior high school level is the introduction of ecosystems with the help of visualization media and interactive games that can encourage student participation in the teaching stage. There was an increase of about 40% in students in the final test indicated by students more actively participating in the game. The results of this service show that teaching activities with a combination of methods such as teaching with storylines, adding distinctive tones, and unique styles, teaching colorful image media, and final tests in the form of games can help improve insight, understanding, and attitudes in environmental awareness.